Analisis Kesalahan Penulisan Kutipan Pada Makalah Mahasiswi PGSD Universitas Negeri Medan - Rahel Valencia Tampubolon; Nurfadhilah Nasution; Deepa Yanti; Indah Aqilah Putri Lubis; Juwita Inggrid Sinaga; Wisman Hadi (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to analyze errors in writing quotations in students' papers from the PGSD Study Program at Medan State University, especially in the paper entitled